Yeast Assimilable Nitrogen Concentrations Influence Yeast Gene Expression and Hydrogen Sulfide Production During Cider Fermentation - Song, Yangbo; Gibney, Patrick; Cheng, Lailiang; Liu, Shuwen; Peck, Gregory (Frontiers in Microbiology, 2020)
The fermentation of apple juice into hard cider is a complex biochemical process that transforms sugars into alcohols by yeast, of which Saccharomyces cerevisiae is the most widely used species. Among many factors, hydrogen sulfide (H2S) production by yeast during cider fermentation is affected by yeast strain and yeast assimilable nitrogen (YAN) concentration in the apple juice. In this study, we investigated. the regulatory mechanism of YAN concentration on S. cerevisiae H2S formation. Two S. cerevisiae strains, UCD522 (a H2S producing strain) and UCD932 (a non-H2S-producing strain), were used to ferment apple juice that had Low, Intermediate, and High diammonium phosphate (DAP) supplementation. Cider samples were collected 24 and 72 hours after yeast inoculation. Using RNA-Seq, differentially expressed genes (DEG) identification and annotation, Gene Ontology (GO), and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment, we found that gene expression was dependent on yeast strain, fermentation duration, H2S formation, and the interaction of these three factors. . For UCD522, under the three DAP treatments, a total of 30 specific GO terms were identified. Of the 18 identified KEGG pathways, “Sulfur metabolism”, “Glycine, serine and threonine metabolism”, and “Biosynthesis of amino acids” were significantly enriched. Both GO and KEGG analyses revealed that the “Sulfate Reduction Sequence (SRS) pathway” was significantly enriched. We also found a complex relationship between H2S production and stress response genes. For UCD522, we confirm that there is a non-linear relationship between YAN and H2S production, with the Low and Intermediate treatments having greater H2S production than the High treatment. By integrating results obtained through the transcriptomic analysis with yeast physiological data, we present a mechanistic view into the H2S production by yeast as a result of different concentrations of YAN during cider fermentation.